Language and intercultural communication in Uzbekistan - Abdullayeva Elina Asanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The study of languages in comparison is one of the most popular areas of modern linguistics. This is the area that pushes the narrow scientific interests of linguistics, gives scope for the study of broad humanitarian problems: the relationship of language and culture, language and national consciousness. This is the knowledge of various unique linguistic cultures, national peculiarities of people's perception of the world and the definition of their place in it. Thanks to this, linguistics (and comparative linguistics in particular) attracts the attention of ethnologists, cultural scientists, psychologists, historians and representatives of many other sciences.